The Use of Japanese Personal Pronoun based on Gender in â€œNarcissuâ€ by Tomo Kataoka - Nusantara, Hadiid Hideo (Universitas Pendidikan Indonesia (Indonesia University of Education), 2020)
This article discussed the difference of Japanese pronouns based on gender from literature point of view. The database of this study was a novel entitled â€œNarcissuâ€ by Japanese author Tomo Kataoka. The research method used in this research was descriptive method. In analysing the novel, author used the morphology theories by Harumi Tanaka (1982). The findings of this study showed that the use of personal pronoun including first-person pronouns, second-person pronouns, and third-person pronouns in the novel were influenced greatly by gender. The difference in using these personal pronouns were caused by the difference in man and womanâ€™s perception. Based on the data, there were tendency that the speakers choose the best word to utter to their interlocutor based on their own perspective, influenced by the situation and the context. The findings of this study was expected to help foreign language learners to understand better about the use of Japanese personal pronoun based on gender, mainly in conversation.